(untitled) (Research, Society and Development, 2020)
Introduction: The Coronavirus disease (COVID-19) has a high lethality rate among the elderly people, who are more vulnerable to novel diseases, especially those kept in Long Term Care Institutions for the Elderly (LTCIs). Objective: To describe and discuss how the current social isolation imposed by the pandemic has impacted the senior citizens residing in Brazilian LTCIs. Methodology: Primary research was carried out employing the PubMed and SciELO databases, using the keywords “Coronavirus infection” and “Institutionalized elderly health” and with the keywords “COVID-19" and “Institutionalized elderly” and their respective correlatives in English to search for articles published until September 2020. Results and Discussion: Five Scientific Articles, one Research Note, one Epidemiological Bulletin, and one Technical Note were organized in a table to display their findings. Additionally, other applicable data was collated directly from the hands-on experience of one of the authors, who undertook preceptorship for Physiotherapy interns at a Brazilian LTCI. These institutions can possibly potentiate the propagation and dissemination of this viral disease, therefore, the presently enforced prophylactic strategies, (e.g. social distancing), are essential to help maintain the well-being of the population, even if this may be a detriment to their quality of life. Conclusion: The limitations imposed on social interactions by the pandemic have a negative impact on the cognitive and physical aspects of the elderly people at the LTCIs, who already experience conditions of exclusion and isolation.